Knowledge, attitude and practice regarding osteoarthritis management among physicians of primary health care centers; Al-rusafa/ Baghdad/2017 - Tawfeeq, Aseel Kareem (AL-Kindy College Medical Journal, 2019)
Background:-Osteoarthritis (OA) is the most common form of arthritis and the leading source of physical disability in elderly people. The Prevalence of OA is increasing and will continue to do so as the population gets older. The OA is predominantly managed in primary care centers by primary health care physicians and much can be done to alleviate symptoms from osteoarthritis by combinations of therapeutic options including pharmacological and non-pharmacological treatments. Objectives of study :- To assess the knowledge, attitude and practice of Iraqi PHCC physicians in Baghdad, AL-Rusafa, regarding the management of osteoarthritis patient, and it’s association with sociodemographic data. Methods:- A descriptive cross sectional study with some analytic elements has been conducted from the 1st of January to 1st of June 2017, in primary health care centers of six sectors selected randomly from Al Rusafa health directorate; in Baghdad. The data was collected by self-administered questionnaire regarding demographic characteristics, knowledge, attitude, and practices of physicians regarding management of osteoarthritis. Data analysis was done by (frequency, percentage), Chi square test (Fisher exact test). P value less than 0.05 was considered significant . Results: The total study sample was 204 enrolled physicians, their age ranged from (25-58) years, The correct answers regarding etiology, diagnosis, imaging findings etc. ranged from 64.2-83.3% which reflect good knowledge of physicians regarding OA disease as well as that highly qualified physician showed good knowledge, about half of enrolled physicians showed good attitude and their practices regarding osteoarthritis and its management are good in general. Conclusion; -The knowledge, attitude and practice regarding osteoarthritis managent among primary health care physicians are good in general.